2017
DOI: 10.3390/jcm6100098
|View full text |Cite
|
Sign up to set email alerts
|

Production and Use of Hymenolepis diminuta Cysticercoids as Anti-Inflammatory Therapeutics

Abstract: Helminthic therapy has shown considerable promise as a means of alleviating some inflammatory diseases that have proven resistant to pharmaceutical intervention. However, research in the field has been limited by a lack of availability to clinician scientists of a helminth that is relatively benign, non-communicable, affordable, and effectively treats disease. Previous socio-medical studies have found that some individuals self-treating with helminths to alleviate various diseases are using the rat tapeworm (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The dose finding approach entails starting with a low dose of helminth and then slowly working up to higher doses until either (a) symptom relief is obtained or (b) adverse side effects are sufficient to warrant backing off on the dosage or cessation of the protocol. This dose-finding protocol has been described previously for HDCs (10). Dose finding is also readily achieved for TSO given its stability during storage in a liquid suspension and relative frequency of administration on a weekly basis.…”
Section: One Size Does Not Fit All: the Effective Dose Of Helminth Vamentioning
confidence: 99%
See 2 more Smart Citations
“…The dose finding approach entails starting with a low dose of helminth and then slowly working up to higher doses until either (a) symptom relief is obtained or (b) adverse side effects are sufficient to warrant backing off on the dosage or cessation of the protocol. This dose-finding protocol has been described previously for HDCs (10). Dose finding is also readily achieved for TSO given its stability during storage in a liquid suspension and relative frequency of administration on a weekly basis.…”
Section: One Size Does Not Fit All: the Effective Dose Of Helminth Vamentioning
confidence: 99%
“…Later studies pointed toward the idea that exposure to helminths is also important for the prevention of autoimmune diseases (6,7) and some neuropsychiatric disorders (8). In light of this information, it is perhaps unsurprising that thousands of individuals today use helminths to treat their chronic inflammatory conditions (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tapeworm Hymenolepis diminuta is a good candidate for helminth therapy (Lukeš et al ., 2014) as it cannot autoinfect, does not migrate outside of the intestinal lumen, does not harm the host (Roberts, 1980; McKay, 2010), and it is relatively cheap and easy to produce (Smyth et al , 2017). Importantly, H. diminuta ameliorates inflammatory disease in many, but not all, animal models [reviewed in (McKay, 2015)] and is effective in the majority of self-treating humans (Smyth et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently used by individuals for self-treating of inflammatory bowel disease and other intestinal inflammations and meets criteria for helminth therapy. For this purpose, its life stages are now being produced in semi-industrial amounts (Smyth et al ., 2017). The authors convincingly demonstrated that a controlled infection with H. diminuta indeed protects rats against severe inflammatory colitis by inducing a type 2 immune response, resulting in faster recovery.…”
Section: Current Modelsmentioning
confidence: 99%